THE NOTARY ROLE IN THE IMPLEMENTATION OF A PAWN PAYMENT AGREEMENT ACCORDING TO HABITS OR TRADITION (GA'DE DAE) IN PUKDALE VILLAGE, KUPANG REGENCY, NTT - Risandy, Jelian Isra; Putra, Mohamad Fajri Mekka (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
The implementation of traditional pawn agreements is usually carried out by indigenous groups in several remote areas in Indonesia. An example of the traditional pawn that still exists today is the traditional pawn carried out by the community in Pukdale Village, East Kupang District, Kupang Regency. The community or the parties who make this pawn agreement, should have started to involve a notary in the pawn agreement process, so that it can provide legal certainty guarantees and have perfect power of proof in accordance with the mandate of the law. The research problems in this study are regarding the Urgency of the Role of the Notary in the Pawn Agreement Process according to habit or tradition (Ga'de Dae) in Pukdale Village, Kupang Regency, NTT and the Implementation of the Notary Deed in the Pawn Agreement. The research typology used is exploratory design, and the form of research is Juridical Empirical. While the data analysis method used is a qualitative approach method. The results of the study indicate that the role of the Notary in a Pawn Agreement is indeed very necessary to ensure the strength of the Proof of the Pawn. One of the factors for the occurrence of conflicts or defaults carried out by the parties in the pawn is due to the absence of an authentic deed that can provide separate protection for the parties. The implementation of the Notary Deed in the Pawn Agreement must continue to pay attention to the provisions of the existing legislation, so that the authenticity of the deed is guaranteed. A notary as a public official who makes an authentic deed is responsible for his actions in connection with his work in making the deed.